Investigation of the motion characteristics for a long flexible rotating pipe in flow by IDVM–FEM method - Wei Chen (AIP Publishing LLC, 2021)
A long flexible rotating pipe in flow is investigated by using an improved discrete vortex method and finite element method. For the pipe without rotation, the lock-in phenomenon has been confirmed and discussed and the motion characteristics are illustrated at different flow velocities. For the pipe with rotation, the mean position of the long flexible pipe gradually inclines to the cross-flow direction due to the increased lift force. Two different motions (vortex-induced vibration and reverse direction whirl) have been observed. The frequency of vortex-induced vibration remains steady with the increase in the rotation rate. For the reverse direction whirl, the frequency decreases with the increasing rotation rate due to the increased effective added mass.